Methodological Bases of Definitions “Refinancing,” “Recrediting” and Application Practice in Residential Mortgage Lending - Savinova, V. A.; Vagapova, D. Z.; Sorokina, M. G. (International Journal of Economics and Financial Issues, 2016)
A mortgage loan is considered as one of the most difficult forms of credit relations, first of all resulting in need to attract long-term financial resources on the basis of its refinancing. The expansion of foreign banks in the domestic credit markets is accompanied by a high rate of growth of credit investments into the economy of the state, and it leads to disruption of “borders” of credit and a negative impact on its development. At the same time, they are responsible for development of advanced technologies in national credit markets to improve the quality of customer service and modern banking products best suited to their needs, which include relending to borrowers. The purpose of this paper is to study the content and methodological foundations of “refinancing” and “relending” definitions, their relationships, and to identify functional orientation of these concepts in development of mortgage lending. The results of the study deepen the theoretical foundations of mortgage, the methodological tools used in practice of mortgage lending in relation to considered definitions, which allows specifying their content and developing ways of improvement. Keywords: Refinancing; liquidity; Interest rate; Relending; Financial and lending practices; Financial and credit instruments. JEL Classifications: G00; G21